AN ALTERNATE PROOF OF WISE'S MALNORMAL SPECIAL QUOTIENT THEOREM. (12th January 2016) - AGOL, IAN; GROVES, DANIEL; MANNING, JASON FOX
Abstract : We give an alternate proof of Wise's malnormal special quotient theorem (MSQT), avoiding cubical small cancelation theory. We also show how to deduce Wise's Quasiconvex Hierarchy Theorem from the MSQT and theorems of Hsu and Wise and Haglund and Wise.